2021
DOI: 10.1212/cpj.0000000000000950
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Cognitive Outcomes in Tuberculous Meningitis

Abstract: ObjectiveData on cognitive changes in patients of tuberculous meningitis (TBM) are sparse. We aimed to study the cognitive profile of grade I TBM patients and correlate with the cytokine values.MethodsProspectively 60 (M:F-31:29) patients of grade I TBM were recruited. Clinical details, CSF estimation of cytokines, neuropsychological assessment was done and correlation were done.ResultsMean age of presentation and duration of symptoms were 32.2 (32.2 ± 10.1) years and 29.9 (29.9 ± 25.9) days respectively. Defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…12 HIV-P patients who have cognitive changes need to be suspected of having TBM. 14 With low CD4 and immune response, tuberculomas do not form, this causes the clinical presentation to be subtle in the form of neurocognitive changes. 10,13,18 Cognitive functions that are disturbed are attention, executive function, memory short-term, and learning memory.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12 HIV-P patients who have cognitive changes need to be suspected of having TBM. 14 With low CD4 and immune response, tuberculomas do not form, this causes the clinical presentation to be subtle in the form of neurocognitive changes. 10,13,18 Cognitive functions that are disturbed are attention, executive function, memory short-term, and learning memory.…”
Section: Discussionmentioning
confidence: 99%
“…Other compromised tests included the spatial span test (50%), clock drawing test (48.3%), digit span test (35%) and the colour trail test 1 and 2 (30% and 33.3%, respectively). 14 After a 1-year follow-up, a neuropsychological evaluation of 43 patients (71.6%) revealed that 58.1% of the patients had impairment on one or two tests, and 32.5% had impairment on three or more tests. In all the assessed domains, four patients (9.3%) received normal neuropsychological evaluations.…”
Section: Characterization Of Demographic and Quality Of Assessmentmentioning
confidence: 97%
See 2 more Smart Citations
“… 199 , 200 Another recent prospective study of 60 adults with TBM reported varying degrees of cognitive impairment in more than 90% of 43 patients tested at 1 year follow-up. 201 …”
Section: Post-tb Neurological Disabilitymentioning
confidence: 99%